The innovating firm as corporate entrepreneurship. Issue 4 (10th July 2017) - Urban, Boris; Wood, Eric
Abstract : Purpose: Innovation is a multi-dimensional phenomenon and at the firm level incorporates the behaviors and interactions of individuals and various organizational factors. Not only are entrepreneurship and innovation complementary, but a combination of the two is vital to organizational success. The purpose of this paper is to respond directly to research calls to provide an integrated model of corporate entrepreneurship (CE) which encompasses both organizational- and individual-level factors. Design/methodology/approach: A model was formulated in accordance with the study hypotheses and statistically tested. A sample of 784 responses from the South African financial sector was surveyed. Structural equation modeling (SEM) was used to test for model fit. Findings: The results support the hypotheses that it is through the interaction of the firm (in establishing corporate building blocks), and the individual (through entrepreneurial alertness and metacognitions) that CE activity is realized. SEM results showed that entrepreneurial alertness had the greatest direct path impact on CE. Practical implications: Managers need to understand and leverage corporate building blocks in a manner that influences employee's respective levels of entrepreneurial alertness and metacognitions in order to foster CE. Originality/value: The study is one of the first to model and empirically test causal links between corporate building blocks, entrepreneurial alertness, metacognitions, and CE at the firm level. Moreover, the study takes place in an under-researched African context, allowing for fresh insights to evolve.